(untitled) (The Peerian Journal, 2025)
This extensive study examines the role of the Abbasid Caliphate during the first and second periods in managing seaports in Iraq and the Arabian Peninsula, and how it dealt with the natural and logistical challenges facing international maritime trade during that era. The study highlights how the Caliphate sought to integrate ports into a flexible international trade network based on smart policies for maritime protection, financing the construction of docks, exempting merchants, and developing navigation methods. The study also addresses the types of goods exchanged, which included spices, luxury fabrics, wood, gold, ivory, and pearls. The study monitors floods, sea storms, and shifts in tidal lines that affected Abbasid ports, and how the caliphs responded to them through comprehensive plans, such as moving warehouses to higher hills, redesigning docks, and opening alternative routes. It also highlights the recovery of the private commercial sector through financial incentive measures. The study also highlights some of the Abbasid military strategies to confront pirates. The study relies on academic narrative documentation to demonstrate how the policies of the Abbasid caliphs contributed to building a flexible global maritime trade system. Efficient and able to absorb natural and human shocks, it continued to flourish for decades.